Multi-Omics Analysis of the Gut-Liver Axis Reveals the Mechanism of Liver Injury in Colitis Mice - Zhu, Luoyi; Zong, Xin; Xiao, Xiao; Cheng, Yuanzhi; Fu, Jie; Lu, Zeqing; Jin, Mingliang; Wang, Fengqin; Wang, Yizhen (Frontiers in Immunology, 2022)
Liver injury is a common complication of inflammatory bowel disease (IBD). However, the mechanisms of liver injury development are not clear in IBD patients. Gut microbiota is thought to be engaged in IBD pathogenesis. Here, by an integrated analysis of host transcriptome and colonic microbiome, we have attempted to reveal the mechanism of liver injury in colitis mice. In this study, dextran sulfate sodium (DSS) -induced mice colitis model was constructed. Liver transcriptome showed significant up- and down-regulation of pathways linked to immune response and lipid metabolism, respectively. Whilst the colon transcriptome exhibited dramatic alterations in immune response and pathways associated with cell growth and death. The microbiota of DSS-treated mice underwent strong transitions. Correlation analyses identified genes associated with liver and colon injury, whose expression was associated with the abundance of liver and gut health-related bacteria. Collectively, the results indicate that the liver injury in colitis mice may be related to the intestinal dysbiosis and host-microbiota interactions. These findings may provide new insights for identifying potential targets for the treatment of IBD and its induced liver injury.